Fractal impeller for stirred tank reactors - Kulkarni, Amol A.; Jha, Neha; Singh, Abhishek; Bhatnagar, Sumit; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2011)
Stirred tank reactors are used for variety of applications at different scales of operation. The conventional impellers tend to develop regions having nonuniform energy dissipation rates in the stirred reactor. In this work, we propose a novel fractal impeller, which helps in reducing such nonuniformities and help develop a uniform randomness throughout the reactor. The impeller geometry is discussed in detail. Experimental measurements of the power consumption, mixing time, suspension quality, and the ability for gas dispersion were carried out, and the performance is compared with the conventional impellers. The impeller is seen to have a low power number, and it can generate a uniform suspension of particles even at relatively lower impeller speeds and can efficiently disperse gas into liquid to yield relatively higher gas hold-up values. The Fourier analysis of the power consumption time series data indicates that no specific prominent frequency events exist in the reactor, and the spectrum showed several frequency events to exist in the reactor with almost identical prominence.